Use of the Sport Concussion Assessment Tool 5 (SCAT5) in professional hockey, part 1: cross-cultural normative data - Echemendia, R. J.; Thelen, J.; Meeuwisse, W.; Hutchison, M. G.; Comper, P.; Rizos, J.; Bruce, J. M. (British Journal of Sports Medicine, 2021)
Objectives This paper provides comprehensive normative data stratified by language preference and age on the components of the National Hockey League (NHL) Sport Concussion Assessment Tool 5 (SCAT5) in a multilingual sample of professional ice hockey players and compares the findings from a paper form of the NHL SCAT5 with an electronic (App) version of the tool.